Global polarization of [lambda] and [lambda] [bar] hyperons in Pb-Pb collisions at √sNN=2.76 and 5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; Ohlson, Alice; et al. (Physical review, 2020)
The global polarization of the Λ and ¯¯¯Λ hyperons is measured for Pb-Pb collisions at √sNN=2.76 and 5.02 TeV recorded with the ALICE at the Large Hadron Collider (LHC). The results are reported differentially as a function of collision centrality and hyperon's transverse momentum (pT) for the range of centrality 5-50%, 0.5<pT<5 GeV/c, and rapidity |y|<0.5. The hyperon global polarization averaged for Pb-Pb collisions at √sNN=2.76 and 5.02 TeV is found to be consistent with zero, ⟨PH⟩(%)≈0.01±0.06(stat.)±0.03(syst.) in the collision centrality range 15-50%, where the largest signal is expected. The results are compatible with expectations based on an extrapolation from measurements at lower collision energies at the Relativistic Heavy Ion Collider, hydrodynamical model calculations, and empirical estimates based on collision energy dependence of directed flow, all of which predict the global polarization values at LHC energies of the order of 0.01%.
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, S. Klewin, M.K. Köhler, L. Leardini, N.A. Martin, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband, A. Yuncu [und 1008 weitere]
Gesehen am 19.05.2020
Im Titel ist "lambda" als griechischer Buchstabe dargestellt
Im Titel ist das zweite "lambda" mit Oberstrich dargestellt
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt